HCV Medication Receipt Among Individuals With Methamphetamine, Opioid, and Alcohol Use Disorders in Arkansas, 2018–2022: A Long Road Ahead for HCV Elimination in the US South - Pro, George (Journal of drug issues, 2025)
Background. Methamphetamine and opioid use disorders (MUD/OUD) are increasing in the US, paralleled by a surge in hepatitis C virus (HCV). HCV is curable with direct-acting antiviral medication (DAA), but people with HCV who use drugs often don’t receive it. We estimated differences in DAA by substance type among people with HCV in Arkansas. Methods. We used a statewide medical claims database to identify HCV cases who also had MUD, OUD, and/or AUD (pooled 2018–2022; N = 5439). We used multiple logistic regression to model DAA receipt, adjusted for relevant covariates. Results. Only 10% of our sample received DAA. The lowest predicted probabilities of DAA receipt were among people who used methamphetamine (4.5%) and those covered by Medicaid (5.4%). Conclusion. Arkansas Medicaid has the strictest requirements for initiating DAA in the country. Public health efforts that reduce exposure to HCV among people who use drugs will reduce the HCV burden in Arkansas.